Knowing Without Having The Competence to Do So. (27th February 2019) - Hirvelä, Jaakko
Abstract : According to all varieties of virtue reliabilism, knowledge is always gained through the exercise of epistemic competences. These competences can be conceived as competences to form true beliefs, or as competences to know. I will present a short but decisive argument against the idea that knowledge is always gained through the exercise of competences to know. The competence to know isn't necessary for gaining knowledge.